Echocardiographic wall motion abnormalities in patients with stroke may warrant cardiac evaluation. Issue 7 (25th March 2019) - Yaghi, Shadi; Chang, Andrew D; Ricci, Brittany A; MacGrory, Brian; Cutting, Shawna; Burton, Tina; Dakay, Katarina; McTaggart, Ryan; Jayaraman, Mahesh V; Merkler, Alexander E; Reznik, Michael; Lerario, Michael; et al.
Abstract : Background: The aetiology of wall motion abnormalities (WMA) in patients with ischaemic stroke is unclear. We hypothesised that WMAs on transthoracic echocardiography (TTE) in the setting of ischaemic stroke mostly reflect pre-existing coronary heart disease rather than simply an isolated neurocardiogenic phenomenon. Methods: Data were retrospectively abstracted from a prospective ischaemic stroke database over 18 months and included patients with ischaemic stroke who underwent a TTE. Coronary artery disease was defined as history of myocardial infarction (MI), coronary intervention or ECG evidence of prior MI. The presence (vs absence) of WMA was abstracted. Multivariable logistic regression was used to determine the association between coronary artery disease and WMA in models adjusting for potential confounders. Results: We identified 1044 patients who met inclusion criteria; 139 (13.3%, 95% CI 11.2% to 15.4%) had evidence of WMA of whom only 23 (16.6%, 95% CI 10.4% to 22.8%) had no history of heart disease or ECG evidence of prior MI. Among these 23 patients, 12 had a follow-up TTE after the stroke and WMA persisted in 92.7% (11/12) of patients. In fully adjusted models, factors associated with WMA were older age (OR per year increase 1.03, 95% 1.01 to 1.05, p=0.009), congestive heart failure (OR 4.44, 95% CI 2.39 to 8.33, p<0.001), history of coronary heart disease or ECG evidence prior MI (OR 27.03, 95% CI 14.93 to 50.0, p<0.001) and elevated serum troponin levels (OR 2.00, 95% CI 1.06 to 3.75, p=0.031). Conclusion: In patients with ischaemic stroke, WMA on TTE may reflect underlying cardiac disease and further cardiac evaluation may be considered.